Does local endometrial injury in the nontransfer cycle improve the IVF-ET outcome in the subsequent cycle in patients with previous unsuccessful IVF? A randomized controlled pilot study - Sachin A Narvekar; Neelima Gupta; Nivedita Shetty; Anu Kottur; M S Srinivas; Kamini A Rao (Wolters Kluwer Medknow Publications, 2010)
Background: Management of repeated implantation failure despite transfer of good-quality embryos still remains a dilemma for ART specialists. Scrapping of endometrium in the nontransfer cycle has been shown to improve the pregnancy rate in the subsequent IVF/ET cycle in recent studies. Aim: The objective of this randomized controlled trial (RCT) was to determine whether endometrial injury caused by Pipelle sampling in the nontransfer cycle could improve the probability of pregnancy in the subsequent IVF cycle in patients who had previous failed IVF outcome. Setting: Tertiary assisted conception center. Design: Randomized controlled study. Materials and Methods: 100 eligible patients with previous failed IVF despite transfer of good-quality embryos were randomly allocated to the intervention group and control groups. In the intervention group, Pipelle endometrial sampling was done twice: One in the follicular phase and again in the luteal phase in the cycle preceding the embryo transfer cycle. Outcome Measure: The primary outcome measure was live birth rate. The secondary outcome measures were implantation and clinical pregnancy rates. Results: The live birth rate was significantly higher in the intervention group compared to control group (22.4% and 9.8% P = 0.04). The clinical pregnancy rate in the intervention group was 32.7%, while that in the control group was 13.7%, which was also statistically significant ( P = 0.01). The implantation rate was significantly higher in the intervention group as compared to controls (13.07% vs 7.1% P = 0.04). Conclusions: Endometrial injury in nontransfer cycle improves the live birth rate,clinical pregnancy and implantation rates in the subsequent IVF-ET cycle in patients with previous unsuccessful IVF cycles.